Complex Anorectal Disorders Investigation and Management - Wexner, Steven D.; Wexner, Steven D.; Zbar, Andrew P.; Zbar, Andrew P.; Pescatori, Mario.; Pescatori, Mario. (Springer London : Imprint: Springer, 2005)
A large cross-section of the world’s great and good in colorectal surgery have been enticed, inveigled, I suspect at times brow-beaten, to produce this tour de force. The editors, themselves famous for their own extensive contributions in this area, must be congratulated for their ?ne achievements. Every card-carrying specialist needs a reference book of this sort. My own are well worn by many years’ reference, for when confronted by big problems, big issues, senior clinicians must be able to lay their hands on a well-thumbed old favourite: not a small,“where are we now” sort of book, or an exam crammer, but on one that is large, sedate and of “traditional build. ” Rather than being a supergiant covering all of colorectal surgery, this book has focused on the broad structural investigation of the anorectum and on the focused management of largely “functional” problems. And it has done so in style. For this is a core area of specialist practice;your more general colleagues may think twice before referring you new cases of cancer and in?ammatory bowel disease (both also central areas in colorectal surgery), but they will not hesitate in referring the patients whose inves- gation and management are described here. And they will expect you to know how to deal with them. These are some of the most challenging patients to manage. Rightly have the editors covered the physiological areas,rightly the psychological issues, rightly the medicolegal aspects: here is the making of a specialist—the sword and the shield.